Challenges Encountered by EFL Students in Writing their Master Dissertation: The Case of Second-year Master Students at Frères Mentouri University, Constantine 1 - BOUHALI, Sabrina; BELOUAHEM, Riad (Journal of Human Sciences, 2025)
The present study aims at investigating the challenges encountered by Second-year Master students at the Department of English, at Frères Mentouri University, Constantine 1, during the dissertation writing process. The sample consisted of 61 second-year Master students enrolled in the department during the academic year 2023-2024. The data were collected through an Online questionnaire which was sent to the students via e-mail and WhatsApp. The findings revealed that the students faced many challenges among which was finding the related literature, choosing the appropriate methodology, as well as collecting, analyzing, and interpreting data. This study suggests that students’ awareness of the conventions that govern the writing of a dissertation should be raised, and that the students need an additional training on how to get access to reliable databases, how to manipulate the different referencing techniques, and how to use the different data collection and data analysis tools.